Floor plan manual housing. - Schneider, Friederike, ....-; Heckmann, Oliver, ....- (Basel : Birkhäuser, 2011)
From the standardized floor plans of the 1960s to the more individual concepts of the 1980s and the changed requirements and housing types of recent years, example by the detailed typological description of the relevant housing types. Every project is presented with its typical floor plans to a scale of 1:200; sections, site plans, and photographs illuminate each building s structure and situation. In addition to incorporating some forty new projects, this new edition now contains figure-ground diagrams that highlight the most salient features of the floor plans, making them even easier to compare.
Keywords: Architectuur; Bouwkunde; Bouwplanning; Woningbouw